A Correlation Study between Two Adjacent Same-Meridian Acupoints after Laser-Needle Acupuncture with Optical Coherence Tomography and Diffuse Reflectance Spectra - Wu, Xiuli (Evid Based Complement Alternat Med, 2016)
This study is to investigate the correlations among Sanjian (LI3), Hegu (LI4), and Yangxi (LI5) acupoints and their corresponding nonacupoints on the Yangming Large Intestine Meridian of Hand before and after laser irradiation using optical coherence tomography (OCT) and diffuse reflectance spectra. The experiment was conducted on 10 healthy people. A 658 nm laser with 50 mW output power was used for irradiating LI4, LI5 acupoints and their corresponding nonacupoints. As to LI4 acupoint with laser irradiation for duration of 15 or 45 minutes, the OCT backscattered light intensities of LI4 and LI5 acupoints increased significantly, and the reflectance intensities (RIs) of the LI3, LI4, and LI5 acupoints decreased significantly. As to LI5 acupoint with laser irradiation for duration of 15 or 45 minutes, the changes of OCT backscattered light intensities of the corresponding irradiated acupoint and LI4 acupoint increased significantly, and the RIs decreased significantly. However, the OCT backscattered light intensities and RIs for their nonacupoints were almost not changed. The results show that an association exists between two adjacent same-meridian acupoints on the same meridian after laser-needle acupuncture to some extent.